Comparative Study of Sukuk in the Sharia Capital Market: Evidence in Indonesia - Mubarok, Anas Bayan; Witro, Doli; Nurjaman, Muhamad Izazi; Pitriani, Pitriani; Hibaturohman, Iib; Hida, Manarul (Al-'Aqdu: Journal of Islamic Economics Law, 2025)
This article discusses a comparative analysis of mudharabah sukuk, ijarah sukuk, and wakalah bi al-istithmar sukuk. This article aims to highlight and analyse the comparison of mudharabah sukuk, ijarah sukuk, and wakalah bi al-istitsmar sukuk so as to provide answers to the effectiveness and efficiency of the sukuk concept without denying the sharia principles in it. This research is in the form of a comparative study, namely a research procedure that compares interrelated variables by determining their differences and similarities. The data sources used come from books, classical text (yellow book), scientific article, website internet, theses, and fatwas related to the theme the author is taking. The results of the research in the article are: First, there are differences in the characteristics and schemes of mudharabah sukuk, ijarah sukuk, and wakalah bi al-istithmar sukuk, these three sukuk schemes are permissible because they are by predetermined rules. The differences that exist in these three types of sukuk do not mean that they are not allowed to make each other but can be done in different ways. Second, from this comparison, the author sees that investment in sukuk with certainly contract characteristics, especially ijarah sukuk, tends to be safer because of the certainty of the predetermined ujrah. Third, of the three types of sukuk, sukuk with a wakalah bi al-istitsmar scheme tend to be more flexible and easier to understand and implement. The level of risk and profit of the three is different, sukuk with certainly contracts tend to be safer but stable profits and tend to stagnate in contrast to sukuk that use uncertain contracts whose risks tend to be greater but there is a possibility of greater profits.